Mineral Carbonation of CO2 in Mafic Plutonic Rocks, I—Screening Criteria and Application to a Case Study in Southwest Portugal - Pedro, Jorge (2020)
This article describes the screening, ranking and characterization of ultramafic and mafic rocks in southern Portugal for mineral carbonation as an alternative to conventional CO2 storage in sedimentary rocks. A set of criteria including mineralogy, structure, surface area, distance to CO2 sources, expected volume, and socioeconomic conditions was applied to screen ultramafic and mafic rock massifs in the Alentejo region, southern Portugal. Ranking of the massifs indicated that the plutonic massifs of Sines and of Torrão-Odivelas were the most promising. A characterization was made of the Sines massif, a subvolcanic massif composed mostly of gabbros and diorites, located immediately adjacent to the CO2 sources and outcropping along 300 km2 onshore and offshore. These studies confirmed that these rock samples exhibited the appropriate mineralogical and geochemical features, but also indicated that the secondary porosity provided by the fracture patterns was very small.